2013
DOI: 10.1111/tpj.12106
|View full text |Cite
|
Sign up to set email alerts
|

OsCYP2, a chaperone involved in degradation of auxin‐responsive proteins, plays crucial roles in rice lateral root initiation

Abstract: SUMMARYAuxin plays a pivotal role in many facets of plant development. It acts by inducing the interaction between auxin-responsive [auxin (AUX)/indole-3-acetic acid (IAA)] proteins and the ubiquitin protein ligase SCF TIR to promote the degradation of the AUX/IAA proteins. Other cofactors and chaperones that participate in auxin signaling remain to be identified. Here, we characterized rice (Oryza sativa) plants with mutations in a cyclophilin gene (OsCYP2). cyp2 mutants showed defects in auxin responses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 64 publications
(76 reference statements)
1
60
0
Order By: Relevance
“…2), and can move from shoot to root in grafted plants partially restoring the lack of lateral roots in dgt mutant rootstocks [89]. A DGT-like small cyclophilin from Physcomitrella patens is also important for auxin-regulated growth [90], whereas a related cyclophilin from rice (LATERAL ROOTLESS2, LRT2/OsCYP2) plays a crucial role in auxin-regulated lateral root formation [91] and has been shown to directly regulate the stability of the auxin-responsive transcriptional repressor protein, OsIAA11, via peptidylprolyl isomerization [92]. The Arabidopsis cyclophilin CYCLOPHILIN20-2 regulates flowering time by modulating the conformation of BRASSINAZOLE-RESISTANT1 in Ref.…”
Section: Box 2: Immunophilins In Regulation Of Plant Development and mentioning
confidence: 99%
“…2), and can move from shoot to root in grafted plants partially restoring the lack of lateral roots in dgt mutant rootstocks [89]. A DGT-like small cyclophilin from Physcomitrella patens is also important for auxin-regulated growth [90], whereas a related cyclophilin from rice (LATERAL ROOTLESS2, LRT2/OsCYP2) plays a crucial role in auxin-regulated lateral root formation [91] and has been shown to directly regulate the stability of the auxin-responsive transcriptional repressor protein, OsIAA11, via peptidylprolyl isomerization [92]. The Arabidopsis cyclophilin CYCLOPHILIN20-2 regulates flowering time by modulating the conformation of BRASSINAZOLE-RESISTANT1 in Ref.…”
Section: Box 2: Immunophilins In Regulation Of Plant Development and mentioning
confidence: 99%
“…Gly 72 is a highly conserved residue located in the PPIase domain ( Supplementary Fig. 6a) and mutations in this residue of rice LRT2/OsCYP2 and moss PpDGT cause severely impaired auxin signalling 17,30 . Homologous structure modelling based on the crystal structure of wheat (Triticum aestivum) TaCypA-1 (PDB code: 4E1Q) 34 , a cyclophilin sharing 87% identity with LRT2, revealed that Gly 72 is located at the surface of LRT2 immediately adjacent to a b-sheet ( Supplementary Fig.…”
Section: Lrt2 Catalyses Cis/trans Isomerization Of Osiaa11 Peptidementioning
confidence: 99%
“…Mutations in the rice LATERAL ROOTLESS2 (LRT2; also known as Oryza sativa CYCLOPHILIN2 or OsCYP2) gene cause an auxin-resistant phenotype and defective development of lateral roots 16,17 . LRT2 encodes a putative cyclophilin-type peptidyl-prolyl cis/trans isomerase (PPIase) that catalyses the isomerization of peptide bonds at proline residues to specifically regulate protein conformational changes.…”
mentioning
confidence: 99%
See 2 more Smart Citations